2021
DOI: 10.1371/journal.pone.0246069
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on ecological momentary assessment in asylum-seeking children and adolescents resettled to Germany: Investigating compliance, post-migration factors, and the relation between daily mood, sleep patterns, and mental health

Abstract: Background Asylum-seeking children and adolescents (ASCs) resettled to western countries show elevated levels of psychological distress. While research on the mental health of ASCs is increasing, less is known about their day-to-day living experiences such as their daily mood, sleep patterns, and post-migration factors. Moreover, no examination in situ, using smartphone-assisted ecological momentary assessment (EMA), has been conducted up to now among ASCs. Furthermore, we do not know if screening measures suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Whilst a meta-analysis found an association between more prompts per day and higher adherence in clinical samples 44 , prompt fatigue at the daily level was common across studies, with more robust engagement obtained in studies employing weekly or biweekly EMA protocols 45,46 . It may be that the timing and content of prompts is more important than frequency, with the suggestion of smart prompts triggered when an individual is more likely to be receptive and able to respond 47 , allowing convergence of prompt, motivation, and ability as the three elements required for a behaviour to occur 48,49 . Provision of incentives, personalised feedback and gamification were also mentioned as ways to encourage continued engagement 50 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst a meta-analysis found an association between more prompts per day and higher adherence in clinical samples 44 , prompt fatigue at the daily level was common across studies, with more robust engagement obtained in studies employing weekly or biweekly EMA protocols 45,46 . It may be that the timing and content of prompts is more important than frequency, with the suggestion of smart prompts triggered when an individual is more likely to be receptive and able to respond 47 , allowing convergence of prompt, motivation, and ability as the three elements required for a behaviour to occur 48,49 . Provision of incentives, personalised feedback and gamification were also mentioned as ways to encourage continued engagement 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported no significant effect of depression symptom severity on drop out [95,101], EMA prompt response rates 44 , amount of entries / missing data 67 or exclusion due to missing data 76 . Two studies suggested that those with greater depression symptom severity may be less likely to drop out 47 , with continued engagement beyond the minimum time required by the study 115 . Only 1 study found greater depression symptom severity, as well as treatment intensity, to be related to lower use of their smartphone app 101 .…”
Section: How and Why?mentioning
confidence: 99%
See 1 more Smart Citation
“…A sample of 50 participants was estimated to provide statistical power of >.80. were mostly female (n = 28; 57.1%) and self-identified as White (n = 32; 65.3%), multi-racial (n = 7; 14.3%), Hispanic or Latino (n = 3; 6.1%), Native Hawaiian or Pacific Islander (n = 2; 4.1%), Black or African American (n = 1; 2.0%), Asian (n = 1; 2.0%) or other (n = 3; 6.1%). Participants were included in analyses if they responded to at least 35% of EMA signals during the 14-day protocol (based on average compliance rates required for inclusion in prior EMA studies of children and adolescents; Hiekkaranta et al, 2021;Michel et al, 2022;Müller et al, 2021;Parker et al, 2022;van Roekel et al, 2019;Woods et al, 2020), and had accuracy above 0% on at least 50% of completed WM tasks, indicating that responses reflected at least some level of effort. A total of 17 participants were removed from analyses due to low compliance (n = 14) or attrition (n = 3).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies (85%) consisted either exclusively or partially of African American or Black participants. One study (Müller et al, 2021) used a signal-contingent design, where participants were prompted to fill out daily diaries at random intervals by the researchers, while all others ESM studies adopted an intervalcontingent design, in which participants filled out daily diaries in the evening. Number of days sampled ranged from 9 to 58 while the most common sampling period was 14 days (68%, 13 studies).…”
Section: Sample Characteristicsmentioning
confidence: 99%